Equity 101 : culture : book 2 - Linton, Curtis (Corwin, A SAGE Company, 2013)
This book takes on culture: the cultures we come from as individuals and the culture we foster in our schools. It uses real-life success stories as models to recognize inadvertent cultural biases increasing educators' cultural competency, overcoming institutionalized factors that limit achievement, and implementing equitable practices that ensure individualized support for all students.